2017
DOI: 10.17759/autdd.2017150208
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to prevent the birth of a child with autism?

Abstract: Recovery of health in families planning a child and pregnancy support in families at risk of a child with autism are the necessary measures, which, along with the results of researching certain patterns in epigenetic inheritances of autism, lead scientists to conclusions about the possibility to reduce the future birth rate of such children. The results of studying of some of the patterns of epigenetic inheritance of autistic disorders are also lead scientists to those conclusions. A short review of the array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Similarly, a study in Syria confirmed these findings while considering additional factors such as parental kinship, their age, and smoking habits [34]. An intriguing conclusion regarding the increased risk of ASD emerged from a study on planned pregnancies in Ukraine, which factored in geographical location and the prevailing climate [35].…”
Section: Time Dimensionmentioning
confidence: 79%
“…Similarly, a study in Syria confirmed these findings while considering additional factors such as parental kinship, their age, and smoking habits [34]. An intriguing conclusion regarding the increased risk of ASD emerged from a study on planned pregnancies in Ukraine, which factored in geographical location and the prevailing climate [35].…”
Section: Time Dimensionmentioning
confidence: 79%